Difference of the size of average crown width first molar and second molar mandible of the Pawon Man with modern man - Senjaya, Taufik; Oscandar, Fahmi; Yondri, Lutfi (Padjadjaran Journal of Dentistry, 2012)
Introduction: Pawon Man is prehistoric human who was expected life about 9525-5660 BC and have lived in a Cave Pawon located in Mountain Masigit Village, District Cipatat, Bandung Regency. The purpose of this research to analyzed the difference size of average crown width first molar and second molar mandible Pawon Man with Modern Man. Methods: The research used a descriptive method, so that from 4 archives radiograph Pawon man, can be obtained 14 samples radiographs Cone Beam Computed Tomography first tooth molars and second molars mandible. The research conducted on Ez Implant-3D program using a digital ruler, measurement results then recorded in tabular form, then statistically analyzed using independent two-sample t test. Results: The average size of widht crown first tooth molars and second molars mandible were larger for Pawon Man teeth than Modern Man. Conclusion: The average size of widht crown first tooth molars and second molars mandible were larger for Pawon Man teeth, because Pawon Man eating hard food and rough textured with simple food processing, with transition of culture has changed the dietary and food technology, so the shape of the big teeth are no longer needed.